(untitled) (GYMNASIUM, 2009)
The paper presents the factors that have an important impact on the strength of an athlete knee muscle. The paper solves a statically approach of the equilibrium of a leg, emphasizing the major influences of some variables, such as: body weight, angles of the leg with respect to earth, the length of a leg etc. Equation 7 is the mathematical model of the way in which the angle Φ as a function of θ and other variables. Further geometrical conditions will allow computing the force acting on quads and knee joint, as we see in part II.